Mine openings, stability and support - Aldorf, Josef (Developments in geotechnical engineering, 1986)
In this book, the authors present a review of the methods used for the solution of problems of stability and support of mine workings, based on the study and analysis of the validity conditions of individual theoretical computing procedures. The classification of these methods, based on the analysis of factors determining the behaviour of a system of mine openings, should contribute to the greater objectivity of decisions connected with the management and control of mining operations and, from the educational point of view, enable the intricate problems of stability to be better understood. Chapters dealing with support structures and technologies of support review the present state of the art with special reference to problems prevailing in Europe where mining is carried out under continuously deteriorating and less favourable natural conditions. The authors have assembled the theoretical and practical knowledge necessary for those to whom the book is addressed, namely, practising mining engineers and project managers, and students and graduates in mining colleges and schools.